A Practical Journey in Implementing a Shari’ah Compliant Hospital: An Nur Specialist Hospital’s Experience - Md Shariff, Shaharom; Mohtar, Shahimi; Jamaludin, Roslan (IIUM Medical Journal Malaysia, 2018)
Research on Islamic products and services has been receiving great attention over the past years. This has attributed to the increasing awareness among Muslims to consume Halal products or served with Shari’ah compliant services. In responding to this development, An Nur Specialist Hospital has initiated to be the first private Shari’ah Compliant Hospital (SCH), through the award of the MS 1900:2014 in April 2015. MS1900:2014 provides guidelines for an organization to be accredited as a Shari’ah compliant organization. The Ministry of Health, Malaysia has introduced ‘ībādah friendly hospital’ in 2010. However, there is lack of research on the characteristics and implementation of SCH in the healthcare industry. Therefore, the purpose of this paper is to understand the implementation of SCH at An Nur Specialist Hospital. A qualitative case study is utilised to investigate the issues and implementation of SCH. The case study uses in-depth, open-ended interview with the hospital senior management. The interview was recorded, transcribed, and evaluated based on thematic analysis to understand the practice. The study found major outcomes in implementing SCH, such as the important role of the Shari’ah Advisory Council in ensuring all the Standard Operating Procedures are in line with Shari’ah principles, continuous staff development programs in providing the Shari’ah understanding and latest fatwā on Fiqh Medic. The other outcome is the positive response from patients who have been frequently visiting the hospital due to the status of An Nur as a SCH.